The impact of technology on buyer-seller interactions - Leonidou, Erasmia (My University, 2024)
Modern civilized societies are characterized by innovation and rapid technological progress. Digitalization and staggering amounts of information have played a catalytic role in reshaping and reassessing the relationship between informed buyers and sellers. This article explores issues related to the evolving role of the sales force and the decision-making process through multiformat communication. In the same vein, this paper tries to shed light on the skills and competencies that salespeople need in their quest to achieve their goals, ensuring customer satisfaction and loyalty.
Keywords: Sales management; Personal selling